The Pragmatics of Value and Commodity Structures. Issue 3 (September 2017) - Boltanski, Luc
Abstract : Different sociological approaches claiming a close relation to pragmatism have developed over recent decades, emphasizing situated action, the interpretive and reflexive capacities of actors, and their social capabilities. These so-called pragmatic conceptions have often been presented as an alternative to the structuralism that dominated previous decades. Without ignoring the differences between the two approaches, this article seeks to show not only that they can both be usefully applied to the same object, but also that they can be integrated into a unified theoretical framework. The argument is based on recent empirical work devoted to the study of commercial exchange, in particular the relation between price and value. The pragmatic study of exchange situations makes it possible to identify different forms of valuation that are both embedded into the cognitive resources of actors and objectified in arrangements around commodities. From a structural point of view, these forms of valuation can be considered a "transformation group, " in the sense described by Claude Lévi-Strauss. However, this cognitive structuralism cannot help us to understand the changes undergone by these forms over historical time. For this, we must call on another type of structuralism, which might be labeled "systemic" structuralism. This proposes narratives that aim to establish chains of causality between local processes of commodification and the evolutions of capitalism at a global level.